The Resurgence of Colonial Anglicanism: the Colonial Bishoprics Fund, 1840–1 - Strong, Rowan (Studies in church history, 2008)
Revival and resurgence is not simply something that happens to individuals or groups of persons; it is a phenomenon that, takes place within organized communities, institutions, and societies. The Church has existed in history as an organized society of believers, and this institutional dimension of Christianity has frequently shaped Christian history and the influence of Christianity on wider society for better and worse. Indeed, it could be argued that this is the dimension of Christianity which has been most influential historically. However, in the case of the Church of England in the British Empire its organized influence as a Church was seriously curtailed by its restricted and partial institutional existence throughout the eighteenth century in the North American colonies. There it existed without a bishop to provide local leadership and an effective counterweight to local lay elites. When that situation reversed and the British state began to support colonial bishoprics after the loss of the thirteen colonies in the new United States of America, the Church of England remained largely at the mercy of fluctuating political agendas to supply colonial bishops with sufficient legality and infrastructure. However, in the early 1840s the Church of England underwent a resurgence in the British Empire as a consequence of developing a new response to its metropolitan political situation, which initiated a revival in its colonial engagement.